The Association between Skeletal Protrusion and Labiolingual Inclination of Teeth with Anterior Alveolar Bone Thickness by Computed Beam Computed TomographyImages - Ali Hafez Qoran; Roodabeh Koodaryan; Vahid Hassanzadeh; Elnaz Omrani Rad (Isfahan University of Medical Sciences, 2022)
Evaluation of alveolar bone thickness is crucial for proper implant placement and support and aesthetics of soft tissue around implant restorations. The aim of this study was to determine the relationship between skeletal protrusion of jaw and labiolingual inclination of teeth with maxillary and mandibular anterior alveolar bone thickness using computed beam computed tomography (CBCT).Materials & Methods:In this descriptive-analytical study, cone beam computed tomography images were obtained from 100 patients referred to the radiology department of Tabriz Dental School from 2013-2015 before implant insertion. Maxillary and mandibular protrusion was determined by measuring SNA (Sella-nasion-A point) and SNB (Sella-nasion-B point) angles and labiolingual inclination of maxillary and mandibular anterior teeth was determined by measuring U1-NA (Upper 1-Nasion A point) and L1-NB (Lower1-Nasion B point) angles. Then, thickness of buccal bone was measured at three levels: 3 mm below the CEJ (A), the middle part of the root (B) and the apex (C). Data were analyzed by using descriptive statistics (mean and standard deviation) and Pearson's correlation coefficient and p value < 0.05 will be considered statistically significant.Results:Mean thickness of bone was higher at level C than other two levels and lower at level A than others. There is no statistically significant relation between mean maxillary bone thickness and SNA (p value > 0.05) except for B region on canine (Pearson correlation coefficient = 0.305 and p value < 0.05). There is no statistically significant relation between the mean maxillary bone thickness and U1-NA. There is no statistically significant relation between mean mandibular bone thickness and SNB and L1-NB. (p value > 0.05).Conclusion:There was no statistically significant relation between maxillary and mandibular protrusion and labiolingual inclination of upper and lower anterior teeth with alveolar bone thickness